History and Tradition on the Maramureș County football map (period 1980-2016) - Alexandru ILIEȘ; Marin ILIEȘ; Gheorghe Codruț BULZ (Editura Universităţii din Oradea, 2016)
The map of traditional football from Maramureș County, with representation on the national competitions level, is outlined by the analysis of 38 national competition seasons (Ist, IInd and IIIrd leagues) and countys competions seasons (IV-VI leagues) divided on three periods: the socialist one (1980-1989); the transition (post-socialist) one (1990-2000) and the actual capitalist one (2001-2016). The choice of Maramureș County has been made due to the fact that it represented an important polarization center of Romanian sports, especially during the socialist period. The accomplished data base provides quantitative information (number of localities, teams, number of teams, participations etc) and qualitative information (representation level, continuity) on the level of localities represented by football teams in national level competitions. With the help of the methods used and tools verified in the specialty literature, in the analytical part, there are outlined significant aspects for defining "tradition" on the map of football from Maramureș, through the number of seasons, level of participation and the frequency of names associated to each team. Out of the 241 localities from the county, 110 localities have re-drawn the contour of football tradition map of Maramureș County for the period 1980-2016. Each of the three analyzed periods stands out through specific features.